Penyediaan Katalis Cu/ZnO/Al 2 O 3 untuk Katalis Sintesis-Langsung DME - Suryanet Sari Dewi; Aisyah Ardy; Herri Susanto (Prosiding Seminar Nasional Teknik Kimia "Kejuangan", 2017)
Direct synthesis of dimethyl eter (DME) using Cu-based catalyst was studied with varying amounts of Zn for methanol synthesis, and Al2O3 as a component for methanol dehydration. Catalyst was prepared using two methods, i.e. the sol gel co-precipitation and the co-precipitation. Mass ratio of (Cu + Zn) to Al2O3 was held constant of 2. The characterization test indicated that co-precipitation catalyst had a better mechanical strength than sol-gel catalyst.Characteristic analysis (BET, XRD, SEM, and AAS) and activity tests (at 220oC). The sol gel co-precipitation method consisted of a higher portion of crystals 61.1%, while the coprecipitation catalyst had 21.8% crystals.However,the solgelco-precipitation had the smallest surface area of the catalyst 47.8m^2/g, while the co-precipitation had 114 m2/g. From the results of SEM analysis showed that almost all of catalyst texture contained amorf (50-70%) than crystal (20-40%). Catalyst CZA1 contained many amorf (78.2%) than crystal (21.8%), and this is match from XRD analysis. The amount of ZnO contained in catalyst (from the analysis of AAS) is quite far away from the target, this is due to lack of time aging in metal forming ZnO. Aging 6 hours enough for formation of crystal ZnO, but give a smallest surface area (20.4 m^2 /g). Co-precipitation method with aging 2 hours tested its activity in the synthesis of DME varied the active phase and promoter. CZA2 provide the best catalyst activity in the test activation and catalytic reduction process. CO convertion was 16% by CZA2 catalyst at 220oC and 1 bar.